Regional sea level trend budget over 2004–2022 - M. Bouih; A. Barnoud; C. Yang; A. Storto; A. Blazquez; W. Llovel; R. Fraudeau; A. Cazenave (Ocean Science)
Closure of the regional sea level trend budget is investigated over the 2004–2022 time span by comparing trend patterns from the satellite altimetry-based sea level with the sum of contributions, i.e. the thermosteric, halosteric, manometric and GRD (gravitational, rotational, and deformational fingerprints due to past and ongoing land ice melt) components. The thermosteric and halosteric components are based on Argo data (down to 2000 m). For the manometric component, two approaches are considered: one using GRACE/GRACE Follow-On satellite gravimetry data and the other using ocean reanalyses-based sterodynamic sea level data corrected for local steric effects. For the latter, six different ocean reanalyses are considered, including two reanalyses that do not assimilate satellite altimetry data. The results show significantly high residuals in the North Atlantic for both approaches. In a few other regions, small-scale residuals of smaller amplitude are observed and attributed to the finer resolution of altimetry data compared to the coarser resolution of data sets used for the components. The observed strong residual signal in the North Atlantic points to Argo-based salinity errors in this region. However, it is not excluded that other factors also contribute to the reported non-closure of the budget in this area.